MAKING OF WEB-BASED CHEMICAL LABORATORY EQUIPMENT AND MATERIALS INVENTORY APPLICATION - Siti Hanifah; Sari Sari; Ferli Septi Irwansyah (Gunung Djati Conference Series, 2021)
Making of a web-based laboratory equipment and materials inventory information system is conducted to make laboratory administration easier and more efficient. In the industrial era 4.0 where everything is completely digital, it is necessary to facilitate laboratory management so that learning in the laboratory can be controlled easily. The display of the laboratory equipment and material inventory website was made with a display that is easy for users to learn and use. The method used in this research was Design Based Research (DBR) with the ADDIE models (Analyze, Design, Development, Implementation, and Evaluation) which was carried out until the development stage. The results of the validation test from this website obtained rcount value of 0.812. This laboratory equipment and materials inventory application can be used as a supporting tool for practicum administration in the laboratory.